Sistem Pakar Mendiagnosa Penyakit Pencernaan Pada Manusia Menggunakan Metode Forward Chaining dan Certainty Factor - Arif Wijayanto; Indah Susilawati (Universitas Mercu Buana Yogyakarta, 2021)
Digestive disease is the most common disease and often found in health community centers. Digestive diseases attack organs in the digestive system which can interfere the functions of other systems. If ignored, it can make the person’s condition become more severe. To solve the problem, the researcher attempted to design a smart system to help people to early recognize digestive diseases such as GERD, dyspepsia, cholera, hepatitis, appendicitis, dysentery and hemorrhoids. Based on the symptoms fed by the patients into the system, the system will use the forward chaining method and certainty factor as an inference machine that will produce a disease diagnosis. Of 36 patient data tested on the system and matched with the experts’ validation, 34 of them matched. The system has an accuracy level of 94.4% of the tested data. The results are expected to provide an initial medium of consultation to help people diagnose digestive diseases. Keywords: Certainty Factor, Forward Chaining, digestive diseases, expert system.